KARAKTERISTIK FISIKOKIMIA DAN MIKROBIOLOGIS KALEDO DAGING SAPI DI KOTA PALU - Sukisman Abdul Halid; Abdul Rahim (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
The objective of the study was to evaluate the physicochemical and microbiological characteristics of kaledo in Palu City. The study used a completely randomized design and samples were taken at eight micro, small and medium enterprises (UMKM). Each sample had three replicates and therefore there were 24 research samples. Parameters analyzed were water content, ash content, protein content, fat content, and total microbial number. The results showed that kaledo in Palu City had its water content ranging from 64.36 - 69.19%, ash content from 1.28–1.99%, protein content from 23.02–24.97%, fat content from 4.27– 6.64% and total microbial number from 1.54–6.79 log cfu/g.